ENTREPRENEURAL FIGURE OF MOUNT AGUNG TREKKING GUIDES - Mudana, I Gede; Sutama, I Ketut; Widhari, Cokorda Istri Sri (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2017)
Mount Agung with an altitude of 3,142 meters from sea level stood at the coordinates of 8020'27